Biometric studies of Ailia coila (Hamilton, 1822) from river Brahmaputra, Assam, India - Sogoi, Pranab; Chakraborty, S. K.; Bhattacharjya, B. K.; Sharma, S. K.; Ramteke, M. (Indian Journal of Fisheries, 2019)
For the study of length-weight relationship, morphometric and meristic characters, a total of 711 specimens (196 male and 515 female) of the Gangetic ailia, Ailia coila (Hamilton, 1822) were collected from Uzanbazar and Dhubri landing centres of river Brahmaputra, Assam during September 2013 to April 2014. The length and weight of males ranged from 66 to 154 mm and 1.218 to 20.5309 grespectively and that of females ranged from 66 to 161 mm and 1.4344 to18.2907 g respectively. The length-weight relationship was established as   W = 0.002773 L 3.189306 and W = 0.005794 2.86234 for male and female, respectively. The analysis of covariance  showed significant difference in ‘b’ values between sexes and student ‘t’ test indicated positive allometric growth for male and isometric growth for female. The morphometric characters were compared; showed maximum co-efficient of correlation (r) in standard and pre-dorsal length (0.98) while lowest was observed in mandibular barbel length (0.69) against the total length. Based on the study of meristic traits, the fin formula can be written as B6, P12-15, V5-6, C14-18, A61-75, GR17-24. The minor variations in meristic and morphometric characters could be attributed to genetic components and difference in geographical and environmental parameters like temperature and food availability. The study will helpful in identification of stock and stock-specific management strategies of this species in river Brahmaputra, Assam.Keywords: Ailia coila, Brahmaputra, Length-weight relationship, Meristic, Morphometric